2013
DOI: 10.1039/c2ja30306j
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten coil electrothermal matrix decomposition and sample vaporization to determine P and Si in biodiesel by inductively coupled plasma mass spectrometry

Abstract: A tungsten coil extracted from commercially available microscope light bulbs is used to decompose the organic matrix and vaporize biodiesel samples for P and Si determination by electrothermal vaporization inductively coupled plasma mass spectrometry (ETV-ICP-MS). The vaporization cell is connected to a modified sheath gas tube so that sample vapors are mixed with a continuous aerosol flow exiting the ICP-MS nebulization chamber. Helium and H 2 are used with a collision-reaction interface (CRI) to minimize spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Sample losses during the vaporization and atomization steps were observed in a previously published work using a more compact atomization cell to vaporize the analytes in an ETV-ICP-MS procedure [13]. To overcome this problem, the protecting gas flow was interrupted during these steps, which resulted in a more homogeneous temperature around the sample droplet, preventing the abrupt boiling process responsible for sample splashing.…”
Section: Atomizer Conditioningmentioning
confidence: 91%
See 3 more Smart Citations
“…Sample losses during the vaporization and atomization steps were observed in a previously published work using a more compact atomization cell to vaporize the analytes in an ETV-ICP-MS procedure [13]. To overcome this problem, the protecting gas flow was interrupted during these steps, which resulted in a more homogeneous temperature around the sample droplet, preventing the abrupt boiling process responsible for sample splashing.…”
Section: Atomizer Conditioningmentioning
confidence: 91%
“…Chaves et al [12], for example, reported RSD values as high as 20% in biodiesel analyses by ETV-ICP-MS using a graphite furnace as vaporizer. In a recently published work [13], RSDs of 14 and 20% were reported for P and Si determinations in biodiesel by ETV-ICP-MS using a tungsten coil vaporizer. Average repeatabilities for aqueous solution determinations by WCAES are typically in the 5-15% range [14][15][16][17][18][19][20][21][22].…”
Section: Analytical Figures Of Meritmentioning
confidence: 93%
See 2 more Smart Citations
“…Em unidades de refino ou de craqueamento catalítico, cobre, ferro, níquel e vanádio agem como envenenadores de catalisadores. Vanádio e níquel são os elementos traço mais avaliados em óleos combustíveis (CHIRINOS; OROPEZA e GONZÁLE, 2013; AYDIN I; AYDIN F e HAMAMCI, 2013; DONATI et al, 2013a;ELLIS et al, 2011;QUADROS et al, 2010). Em geral, vanádio produz efeitos negativos nos revestimentos refratários, superfícies de metal de diversos fornos, caldeiras, motores e turbinas pela formação de vanadatos.…”
Section: Elementos Metálicos E Metaloides Em óLeo Cruunclassified